Respuesta :

Step-by-step explanation:

[tex] = {(3 \sqrt{ {x}^{2} } )}^{6} [/tex]

[tex] = {(3 {x}^{ \frac{2}{2} } )}^{6} [/tex]

[tex] = {(3x)}^{6} [/tex]

[tex] = {3}^{6} {x}^{6} [/tex]

[tex] = 729 {x}^{6} [/tex]

====================================

[tex]\large \sf \underline{Problem:}[/tex]

Which expression is equivalent to (3√x^2)^6

====================================

[tex]\large \sf \underline{Answer:}[/tex]

The answer is x⁴

====================================

[tex]\large \sf \underline{Explanation:}[/tex]

[tex]( \sqrt[3] {x}^{2} )⁶ \: {The \: cube \: root \: of \: x² \: is \: x^(2/3)} (x^(2/3))⁶ {Now, \: simply \: multiply \: 2/3 \: by \: 6 \: to \: get \: 4.}[/tex]

x⁴

[tex]( \sqrt[3] {x}^{2} )⁶ \: is \: equivalent \: to \: x⁴[/tex]

====================================